Anaerobiospirillum succiniciproducens bacteraemia in a patient with acute lymphoblastic leukaemia - Fadzilah, M.N.; Faizatul, L.J.; Hasibah, M.S.; Sam, I.C.; Bador, M.K.; Gan, G.G.; AbuBakar, Sazaly (2009)
A 17-year-old man with acute lymphoblastic leukaemia had fever and diarrhoea during a febrile neutropenic episode. A spiral-shaped, Gram-negative anaerobic bacterium was isolated from blood, and confirmed as Anaerobiospirillum succiniciproducens by 16S rRNA sequencing. The patient responded to imipenem.